Strategi Pengelolaan Konflik dalam Kepemimpinan Kepala Sekolah Perspektif Islam - Supriadi; Tamrin, Muh.; Jalil, Abdul (Jurnal EMT KITA, 2025)
Conflict is one of the problems faced by many organizations, especially non-profit organizations such as educational institutions (schools). School leaders or principals play an important role in managing conflict in order to achieve the vision, mission and goals of the organization. This article aims to describe first, the nature, activities and management of conflict. Second, the nature and role of school principal leadership. Third, conflict management strategies in the leadership of school principals from an Islamic perspective. The research method used is literature study, researchers collect data from various sources, reduce and analyze, and draw conclusions. The research results show that: first, the essence of conflict is differences of opinion, while conflict activities are related to competition, conflict management is carried out through introspection, evaluation, identification, and knowing options. Second, the essence of leadership is influencing, while the principal's leadership role includes as a formal official, manager, leader, supervisor, administrator, educator, and as staff. Third, conflict management strategies in Islamic perspective principal leadership are leadership perspectives and behavior